Promoting the La solution in 2:14:1-type compound: Resultant chemical deviation and microstructural nanoheterogeneity. (30th January 2021) - Liu, Yongsheng; Jin, Jiaying; Ma, Tianyu; Peng, Baixing; Wang, Xinhua; Yan, Mi
Abstract: RE2 Fe14 B-based (RE, rare earth) permanent magnets containing abundant and cheap La/Ce have attracted intense attention recently. In comparison with Ce that can fully replace Nd in the 2:14:1 lattice, La substitution for Nd has long been limited at a low level. Here we present that through doping La35 Ce65 alloy with the La/Ce ratio in natural mineral, stable 2:14:1 phase can be maintained at 1273 K within the entire substitution range of [(La35 Ce65 ) x (Pr20 Nd80 )1- x ]2.14 Fe14 B (0.6 ≤ x ≤ 1.0, at.%), as verified by composition analysis, microstructural characterization and magnetic measurements. Interestingly, the promoted La solution in 2:14:1 phase induces two unique findings upon coexisting La-Ce-Pr-Nd: i) Compared to Ce that fits well with the nominal concentration, La deviates noticeably from the nominal one; ii) Nanoscale spinodal-decomposition-like phase separation is observed due to different solubilities of La-Ce-Pr-Nd elements in 2:14:1 phase. Above joint effects induce higher Curie temperature than estimation based on the rule of mixture, which delights the prospect of La35 Ce65 alloy in developing low-cost permanent materials.